Loss of c-Cbl expression correlates with de-differentiation status and lymphatic metastasis in gastric cancer - Chuchu Chen; Yi Hui; Yunzhao Chen; Chengjia Qian; Minxuan Sun (Wolters Kluwer Medknow Publications, 2019)
Context: C-Cbl is an important negative regulator of the cell signaling that acts as an adaptor protein and E3 ubiquitin ligase. The role of c-Cbl in development and regulation of human cancer has aroused intensive attention. Aims: In this study, we aimed to assess the correlation between the expression of c-Cbl and clinicopathological parameters and explored the role of c-Cbl in the development and progression of GC. Settings and Design: This is a Pilot study. Methods and Materials: In total, 84 tissue samples including 44 gastric cancers (GC) and 40 matched adjacent normal tissues were collected after surgery. Then tissue microarray (TMA) and immunohistochemistry (IHC) technology were combined to detect the protein expression of c-Cbl. Statistical Analysis Used: Statistical analysis was performed using SPSS 22.0 (IBM Corporation, Armonk, NY, USA). Results: We have studied the correlation between c-Cbl expression and clinicopathological parameters. Our study showed that c-Cbl has a low expression in 61.4% (27/44) of GC tissues, and the incidence of cases was significantly higher than that in adjacent normal tissues (P < 0.0001). In addition, the correlation between c-Cbl expression and gastric carcinoma subtype (P = 0.027), histological type (P = 0.033), Borrmann classification (P = 0.009), histological differentiation (P = 0.0005), lymph node metastasis (P = 0.007), and intravascular tumor thrombus (P = 0.036) has also been revealed. Conclusions: Our results show that c-Cbl is down-regulated in GC tissues compared with normal gastric tissue, which may play an important role in the development and progression of GC.